Deconstructing the Absurdity of Characters in “Waiting for Godot” Drama by Samuel Beckett - Tomi Arianto; Afriana Afriana; Septriani Septriani (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
This article aimed to analyze an absurd drama entitled "Waiting for Godot" by Samuel Beckett. Derrida's theory is used to reveal the complexities contained in the narrative of the drama. This study used a qualitative descriptive method with the technique of deconstruction analysis. The results of this study answer two research variables including binary opposition as a form of deconstruction reading strategy and Arbitrary Relationship as a form of reversal of meaning in the story. There are 6 binary oppositions determined in this deconstruction strategy, namely Existence and ex-absentia, Hope and Despair, Loyalty and betrayal, Friendship and slavery, Perfection and Suffering, Reality and Imagination. Binary opposition is intended to see the relation that has been considered as a single meaning centered on a text. From this hierarchy of those binary opposition deconstruction could be seen that Vladimir and Estragon as the main characters of this drama are representation of the lower class which have been the victims of the Second World War. Absurdity is again present in the relationship between reality and hope. This hopes then leads to a construction of existence that is realized through the narrative character of Godot.